Using historical accounts of harpsichord touch to empirically investigate the production and perception of dynamics on the 1788 Taskin - MacRitchie, Jennifer; Nuti, Giulia (Frontiers in Psychology, 2015)
This article investigates the extent of production and perception of dynamic differences on a French historical harpsichord, extensively revised in 1788 by Pascal Taskin. A historical review reports on the descriptions of two different types of touch found in treatises of the eighteenth century. These two touches (loud/struck and soft/pressed) were used to perform single tones on the lower, upper, peau de buffle registers (the last of which Taskin is credited with having invented) and the coupled 8-foot registers to investigate differences in dynamics. Acoustic measurements show varied differences of up to 11dB for the two types of touch over different pitches in each register. The strongest difference is measured in the first harmonic of note F2 on the peau de buffle. A listening experiment was conducted to test whether these differences are perceivable. Participants performed a discrimination task using pairs of single tones. Participants were able to perform significantly better than chance in correctly identifying whether pairs of single tones were same or different with respect to loudness (t (24) = 12.01, p < .001). Accuracies were influenced by pitch and register, the peau de buffle providing the strongest accuracies over the four registers tested.